Identity and Indigenouspeoples: Opening Alternatives to Patrimonial Discipline - Cortes-Ferreira, C (UNIV CATOLICA TEMUCO, 2023)
In the present context of indigenous articulation and mobilization, cultural heritage has played an important role in the efforts for identity vindication. Considering the above, this essay proposes that cultural heritage is a cultural, historical, and socially specific response to the historical identity issue. In that specificity, indigenous peoples could devise new specific solutions to their identity issues without submitting to assumptions about heritage. The objective is to propose a reinterpretation of cultural heritage that favors a creative openness to deal with the issue of identity. To carry it out, different debates on culture and the use of cultural heritage as a resource for the vindication of indigenous identities are analyzed. The review of these debates makes it possible to identify theoretical and practical difficulties of patrimonialization related to the indigenous identity issue. For the development of the analysis, cultural heritage is understood as a resource that is part of the processes of politicization of culture carried out by indigenous movements. In other words, it does not necessarily seek to discuss the correct definition or use of the culture concept but rather to explore how culture has been used as a political tool. The need to devise new ways of taking responsibility for identity issues is concluded. For this, the idea of seizing the place occupied by the category is proposed to create new solutions to issues related to historical identities without submitting to assumptions about heritage.